Empowering smallholder olive growers in northwest Tunisia through an agroecological business model - Majri, Rihab; Dhraief, Mohamed Zied; Souissi, Asma; Ouerghemmi, Hassen; Dhehibi, Boubaker; Oueslati, Meriem; Frija, Aymen; M. Oumer, Ali; Fendri, Mahdi; Larbi, Ajmi (University of Natural Resources and Life Sciences, 2024)
Olive cultivation is the most important agroecosystem in Tunisia. This agroecosystem is facing tremendous challenges, including climate change, loss of biodiversity, environmental pollution and resource degradation, as well as increasing price volatility with harmful implications for farmers’ incomes, livelihoods, and rural development. Agroecology is considered actually as the mainstream model for transforming agriculture toward more sustainable and resilient agri-food systems within the given economic and political context